Pengaruh Strategi Promosi Melalui Media Sosial, Kualitas Pelayanan dan Word Of Mouth Terhadap Keputusan Pembelian HP OPPO di Kota Medan - Sudarso, Andriasan; Saragih, Lenny Menara Sari; Victor, Victor; Nasution, Sabrina Azura (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the influence of promotional strategies through social media service quality and word of mouth on the decision to buy oppo cellphones in medan city. This research uses quantitative descriptive research methods. Data analysis techniques use classical assumption tests, multiple linear regression analysis, f tests, t tests and coefficients of determination. The population used was taken from OPPO HP users in the city of Medan, while the sample used was taken from the formula of Hairs et al, namely the sample size specified was 21 x 5, which is 105, then the sample used was 105. The results showed that partially the promotion strategy through social media service quality and word of mouth influenced simultaneous purchasing decisions that promotion strategies through social media, service quality and word of mouth influenced purchasing decisions. The magnitude of the coefficient of determination of 0.539 means that the ability of the promotion strategy variable through social media, service quality and word of mouth explains its effect on the purchase decision variable of 53.9%. While the remaining 46.1% are other free variables that were not studied in this study such as price, brand image, consumer satisfaction and others.